EARLY DETECTION OF GENITAL HUMAN PAPILLOMAVIRUSINFECTION IN REPRODUCTIVE-AGED WOMEN: INTEGRATIONOF SELF-SAMPLING AND MOLECULAR BIOMARKER-BASEDTRIAGE (World Bulletin of Public Health, 2026)
Persistent infection with high-risk human papillomavirus (hrHPV) remains the principal etiological factor in cervical carcinogenesis, disproportionately affecting women of reproductive age. Despite the global transition fromcytology-based screening to primary HPV testing, challenges remain in distinguishing transient infections from transforming lesions requiring clinical intervention.
Keywords: High-risk human papillomavirus; Cervical cancer screening; Reproductive-aged women; Molecular triage; DNA methylation biomarkers